Electrochemical Behavior of Gold–Silver Alloy Nanoparticles. Issue 7 (20th May 2016) - Plowman, Blake J.; Sidhureddy, Boopathi; Sokolov, Stanislav V.; Young, Neil P.; Chen, Aicheng; Compton, Richard G.
Abstract: We report the voltammetry of alloy nanoparticles by using cyclic voltammetry to study gold–silver alloy nanoparticles. Through careful comparison with the response of pure gold nanoparticles, pure silver nanoparticles, and their mixture, the contrasting electrochemical behavior of the alloy nanoparticles is established, providing insights into the electrochemical stability of gold–silver alloy nanoparticles in chloride‐containing media. Abstract : Alter ego : Gold–silver alloy nanoparticles are investigated in chloride‐containing media. A significantly altered electrochemical behavior is seen relative to pure gold and pure silver nanoparticles, and restructuring of the alloy nanoparticles is evident on cycling.